An estimate of the manners and principles of the times and other writings - Brown, John, 1715-1766 (Thomas Hollis library., 2019)
"John Brown took aim at England's higher ranks, calling out their lifestyle as "vain, luxurious, and selfish effeminacy" in a vigorous attack in his main work, An Estimate of the Manners and Principles of the Times (1757). This volume also includes four other works by Brown, as well as a tribute to Brown written by Thomas Hollis and Hollis' annotations in his personal copy of Estimate. The introduction, by David Womersley, places Brown's writings and career in the context of eighteenth-century moralism and his annotations will explain now-unfamiliar words and references to contemporary events, circumstances, and personalities"--